CREATION OF FUNCTIONAL COATINGS ON STEEL BY ELECTRIC-SPARK ALLOYING IN COMBINED INTERELECTRODE ENVIRONMENTS - Lobachova, Halyna; Ivashchenko, Yevgen (Problems of Friction and Wear, 2026)
The influence of the combined interelectrode environment composition at the process of electric spark alloying (ESA) by titanium and chromium on the structure, microhardness and wear resistance of the St.3 steel surface layers was revealed. The change in the environment composition occurred in 2 stages according to new technological schemes: argon - nitrogen, propane-butane - argon. An increase in the microhardness of titanium coatings to 6–7 GPa, and chromium coatings to 5–5.2 GPa was established due to the presence of nitrides (TiN, CrN) and carbides (TiC, Cr7C3) in them. The wear resistance of samples with coatings under friction-sliding conditions without lubrication for 5 hours is 6.14–10.32 times greater than the value of untreated St.3 steel.